Peripheral Arterial Disease and Its Associated Factors among Type 2 Diabetes Mellitus Patients at Debre Tabor General Hospital, Northwest Ethiopia - Yonas Akalu; Ambaye Birhan (Journal of Diabetes Research)
Background. Peripheral arterial disease (PAD), one of the major macrovascular complications of diabetes, is associated with cardiovascular mortality and a high rate of disability following the amputation of an extremity in diabetes patients. However, there is no data on the prevalence of PAD among type 2 diabetes patients in Ethiopia. Therefore, the current study is aimed at determining the prevalence and associated factors of PAD among type 2 diabetes patients at Debre Tabor General Hospital, Debre Tabor, Northwest Ethiopia. Methods. An institution-based cross-sectional study was conducted among type 2 diabetes mellitus patients from February 1 to August 30, 2019. A pretested interviewer-administered questionnaire was used to collect the data. The presence of stenosis and its grading were determined by color Doppler ultrasonography. Data were entered using EpiData-V.4.6 and analyzed by STATA-14. Bivariable and multivariable logistic regression was performed to identify associated factors of peripheral arterial disease. Adjusted odds ratio (AOR) and its confidence interval were estimated for potential predictors included in the final model. P≤0.05 was used to declare statistical significance. Results. The mean age of the study participants was 61.2±7.3 years. One hundred seventy-two (61.4%) patients were males. The prevalence of PAD in this study was 30.7% (95% CI (25.3-36.2%)). Of these, 37 (43%) were symptomatic. Age (AOR=1.09, 95% CI (1.03-1.16)), higher HbA1c (AOR=1.97, 95% CI (1.03-3.40)), being an ex-smoker (AOR=4.68, 95% CI (1.93-11.30)), and current cigarette smoking (AOR=5.84, 95% CI (1.79-19.04)) were significantly associated with PAD. Conclusion. The prevalence of peripheral arterial disease among type 2 diabetes patients was high. Increasing age, high HbA1c, and being cigarette smokers increase the likelihood of developing peripheral arterial disease. Clinicians should prevent PAD; screen T2DM patients who are aged, with high HbA1c, and cigarette smokers; and treat them timely.